Political Role of Muslims Students and Women During Pakistan Moment 1936-1947 - Akhtar, Dr. Sohail; Saleem, Bashaa; Sirwar, Azhar Maqsood (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Hundred years of Muslim’s rule in subcontinent has become end with the tragic story of decline. The rulers of time turned into slaves and their condition has become miserable. The new colonial masters oppressed them and used all tactics to crush them. As a result, Muslims lost their social, religious, political and cultural greatness, according to William Hunter, Muslims have changed from the richest class to the poorest. After the evolution of the two-nation theory, they felt the need to re-establish their identity and then decided on a political struggle. After the Allahabad address of 1930, when Quaid-e-Azam took over the political leadership, he soon realized that all sections of the Muslim community in the society must be involved in the political struggle. With this objective in mind, it was decided to set up the Muslim Students Federation and the Muslim League W omen's Branch. After their establishment, students and Muslim women performed their duties and responsibilities well. They played a key role in the struggle. It was their work that they transformed Muslim League into an electoral party. Student over women turned the successful election campaign of 1945-46 into a successful political struggle. During this time, Muslim students and women thwarted government tactics through their political roles. And the creation of Pakistan is due to their full political will. This paper highlights the political struggle of Muslim students and women during freedom moment of Pakistan.